Exploring Kantara’s Pan-India Connect –How Regional Cinema Touched a Chord and Enthralled Audiences, Nationally - Narain, Shefalika (Journal of Harbin Engineering University, 2023)
The real-life success story of Kannada film, Kantara, is right out of a fiction film. Made by Rishab Shetty, known mainly within the South Indian film circuit, the film had a plot revolving around the local tradition of coastal Karnataka – bhootha kola – where the performer invokes the local deity and becomes the medium between man and God. Mounted on a modest budget of 16 crore, Kantara came out of nowhere to smash records and rake in over 400 crore, worldwide, becoming the 3rd highest grossing Indian film of 2022. Not only did Kantara have Kannada audiences cheering in the aisles, the strong word of mouth resulted in film lovers across languages and regions – Andhra Pradesh, Telangana, Tamil Nadu, Kerala, and North India – flocking to the theatres, with the film being dubbed in multiple languages. This paper tries to analyse reasons behind the mind-boggling national popularity of Kantara. Data from both primary and secondary research have been used. Primary data includes a survey. Secondary data includes articles, statistics and interviews connected to the film. The author attempts to decode how a film with the entirely regional theme of bhootha aradhane resonated strongly with audiences pan-India to shine light on Kannada cinema.
ISME
Keywords: Audience Connect; Bhootha Kola; Kannada; Kantara; Pan-India; Regional Media